p53 protein expression and risk factors in breast cancer – a retrospective study - Shahruddin, Rashidah (2017)
Numerous studies showed that overexpression of p53 protein may be involved in a variety of human malignancies including breast cancer. In breast cancer patients, a mutated p53 gene that encodes the p53 protein is associated with a higher risk of carcinogenesis and this study examine the potential role of p53 status in breast cancer tissues, specifically its association to established risk factors race, age, age at menarche, hormonal factors and cancer grade. The immunohistochemistry (IHC) technique was used to detect overexpression characteristics of p53 protein and the immunohistochemical results were compared with established risk factors. Analysis conducted on 111 breast tissues showed 40% (44/111) positive p53 (+) protein and 60% (67/111) non-expression p53 (-) respectively. Malay occupied nearly half the number of respondents for overexpressed and nonexpression of p53 (+,-) protein (n=53, 48%) followed by Chinese (n=30, 27%) and Indian (n=28, 25%) with no significant difference (p> 0.05).